(untitled) (Global Journals of Research in Engineering, 2023)
Measured resistivities of produced silicide showed their good conductive properties The calculation of technological route for obtaining thin silicide contacts 100A0 in multilayer metallization of Si substrate was carried out and the optimal technological regimes for obtaining Pd Pt and Ni silicide in single-layer metallization of Si substrate were determined